Korean tigers in Honduras: Urban economic zones as spatial ideology in international policy transfer networks. (October 2019) - Martin, Bridget; Geglia, Beth
Abstract: In 2012, the Honduran government and the state-run Korean International Cooperation Agency (KOICA) reached an agreement though which KOICA would provide 4 million to conduct a feasibility study and master plan for three major Special Economic Development and Employment Zones (ZEDEs) in Honduras's Valle department in the southern part of the country. While post-coup right-wing regimes in Honduras seek legitimacy through association with the South Korean "Asian Tiger" and its conformity to global "rules and norms", South Korean zone boosters engage in planning projects overseas as a form of speculative aid potentially opening up new frontiers of investment and development. Drawing on interviews with key actors and ethnographic fieldwork in both Honduras and South Korea, this paper explores representations of urban economic zones through the pinhole of international policy transfer between these two different political regimes. Rather than theorizing urban economic zones as a coherent mobile policy object proliferating in a world of neoliberal globalization, we propose a conceptualization of contemporary urban economic zones as a traveling spatial ideology. The political project of representation–comprised of spectacle and fantasy on one hand, and the erasures and exclusions of abstraction on the other–is a crucial precursor to the material transformations of land dispossession and the re-ordering of space.